2018
DOI: 10.1155/2018/1284234
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Composting of Solid Waste at Household Level in Masaka Municipality, Central Uganda

Abstract: The domestic solid waste stream composition of urban settings in many developing countries including Uganda is largely biodegradable in nature, and thus, composting provides the most suitable solid waste management option for these wastes. However, there is limited information about waste composting at the household level and associated determinants in Uganda. A cross-sectional study was employed to collect quantitative data from 368 residents of Masaka municipality, Central Uganda. A semistructured interviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 12 publications
2
15
2
1
Order By: Relevance
“…is is understandable as the slum community is largely a residential area, as such biodegradable waste from the kitchen is often generated. Our findings are similar to those of studies carried out in other parts of Uganda [10,11,24,25]. However, it is clear from our findings that few households engaged in segregation of biodegradable waste from other types.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…is is understandable as the slum community is largely a residential area, as such biodegradable waste from the kitchen is often generated. Our findings are similar to those of studies carried out in other parts of Uganda [10,11,24,25]. However, it is clear from our findings that few households engaged in segregation of biodegradable waste from other types.…”
Section: Discussionsupporting
confidence: 91%
“…Projects implemented in slum communities sensitize households on solid waste management especially separation at the point of practice [27,28], but many households may not afford multiple receptacles required to segregate waste [29]. Unlike our research, a related study found that a relatively high number of households were willing to engage in waste segregation [10] and in another, half of the respondents segregated their waste [11]. Solid waste segregation allows further processing and value extraction through recycling and composting [30].…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…However, a number of challenges still stand in the way of this realization. Notable among these obstacles are that organic wastes are not separated at source and urban residences are too small to manage them within their compounds as also observed in Uganda [7]. Furthermore, the City does not have composting spaces in its solid waste management dumpsite at Kachok.…”
Section: Nutrient Contentmentioning
confidence: 99%